Thermal Vibration of Thick FGM Circular Cylindrical Shells by Using Fully Homogeneous Equation and TSDT (Global Journals of Research in Engineering, 2025)
The third-order shear deformation theory TSDT effects on functionally graded material FGM thick circular cylindrical shells with entirely homogeneous equation under thermal vibration were investigated by using the generalized differential quadrature GDQ method The nonlinear coefficient term of displacement field of TSDT was used in the equations of motion for thermal vibration of FGM thick circular cylindrical shells Parametric effects of environment temperature and FGM power law index on the thermal stress and centre deflection of FGM thick circular cylindrical shells were investigated
Keywords: shear deformation theory; sinusoidal; stress; displacement; environment temperature; shear correction coefficient